Bioaccessibility and bioavailability of phytochemicals: Influencing factors, improvements, and evaluations. (February 2023) - Hu, Yao; Lin, Qianzhu; Zhao, Hui; Li, Xiaojing; Sang, Shangyuan; McClements, David Julian; Long, Jie; Jin, Zhengyu; Wang, Jinpeng; Qiu, Chao
Abstract: Many phytochemicals with beneficial physiological activities have limited bioavailability due to their poor solubility and stability characteristics. The bioactivities of phytochemicals could be impacted during liberation, digestion, absorption, distribution, metabolism, and excretion processes after their oral ingestion. And the food matrix and processing significantly affect their solubility, chemical degradation, and absorption within the gastrointestinal tract. Researches indicated that the bioavailability of phytochemicals can be enhanced by controlling the composition and structure of food matrices, as well as optimizing food processing operations. Moreover, chemical modification and encapsulation approaches were reported with ability improving the dispersibility, stability, bioavailability, and bioactivity of phytochemicals. Especially for a range of encapsulation technologies are available for this purpose, such as biopolymer nanoparticles, emulsions, liposomes, solid lipid nanoparticles, and nanostructure lipid carriers, which can be assembled from food grade carbohydrates, proteins, and/or lipids. In addition, the experimental methods commonly used to evaluate the bioaccessibility and bioavailability of phytochemicals are reviewed. Utilization of these methods allows screening of food formulations with different structures and compositions, thereby facilitating the optimization of their performance. This review aims to provide information that will guide future research and development efforts on the creation of more effective phytochemical delivery systems. Graphical abstract: Image 1 Highlights: Phytochemicals experienced digestion, absorption, distribution, metabolism, etc. Food matrix and processing influence the biological benefits of phytochemicals. Chemical modification improves the performance of bioactive phytochemicals. Encapsulation could enhance the bioaccessibility of phytochemicals effectively. In vitro/vivo evaluations are used to assess the biological fate of phytochemicals.